Randomized controlled trial to assess medication adherence and health-related quality of life through a collaborative pharmacist-psychiatrist approach to patient education in patients with depression in India - Mishra, Ambed; Kishor, Manohar Rao; Ramesh, Madhan (Frontiers in Psychiatry, 2025)
BackgroundDepression is a common but severe mental health disorder affecting individuals globally. Medication non-adherence and low health-related quality of life (HRQoL) are the major challenges associated with the treatment of patients with depression.Materials and methodsA prospective Randomized Controlled Trial (RCT) was conducted in the psychiatry outpatient department of a tertiary care hospital for six months. Patients were assigned to either a control group receiving usual care or a test group receiving collaborative care using simple randomization technique. The eligible patients diagnosed with depression were enrolled and the data were collected from patient’s care records, prescriptions, patient interviews, patient representatives and healthcare professionals. The intervention in the test group consisted of comprehensive patient education, including a thorough counseling session with a research clinical pharmacist. Counseling sessions included information on the disease, medications prescribed, possible side effects, compliance with medications and overall treatment. The data collected from both patient groups was analyzed for medication adherence using the Medication Adherence Rating Scale (MARS) and health-related quality of life (HRQoL) using the WHOQOL-BREF questionnaire. Statistical analyses were performed using a student t-test with a significance level of P value < 0.05.ResultsThe collaborative care group showed a statistically significant improvement in medication adherence, with a mean increase of 1.67 ± 0.25 (P < 0.001), compared with a mean increase of 0.69 ± 0.05 (P < 0.05) for the usual care group. Similarly, HRQoL scores also improved significantly more in the collaborative care group, with a mean increase of 28.01 ± 2.05 (P < 0.001), compared with a mean increase of 12.46 ± 0.26 (P < 0.05) for the usual care group.ConclusionThis study concluded that pharmacist–psychiatrist collaborative patient education can significantly improve the medication adherence and HRQoL of the patients with depression. Statistically significant increases in medication adherence and HRQoL were observed in the collaborative group.